2020
DOI: 10.1002/jsfa.10514
|View full text |Cite
|
Sign up to set email alerts
|

Impact of processing on the nutritional and functional value of mandarin juice

Abstract: Background: Although phenolic compounds have a role in the health benefits of fruit juice consumption, little is known about the effect of processing on their bioaccessibility. The release of phenolic compounds from the food matrix during digestion is an important pre-requisite for their effectiveness within the human body, so it is fundamental to identify technological treatments able to preserve not only the concentration of phytochemicals but also their bioaccessibility. In this study we investigated the im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 45 publications
4
12
0
Order By: Relevance
“…In any case, the bioaccesibility values obtained for the VI apples were considerably higher than expected; this could be related to the microbial activity of the lactobacillus strain. This is in line with the findings of Di Nunzio et al [ 21 ], who reported a significant increase in narirutin and didymin bioaccessibility by adding 8 log cfu mL −1 of L. salivarius to ortanique juice homogenized at 20 MPa. As was also argued by these authors, this result can be attributed to the ability of the microorganism to enhance the release of phenolic compounds linked to fibers and other components of the food matrix.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…In any case, the bioaccesibility values obtained for the VI apples were considerably higher than expected; this could be related to the microbial activity of the lactobacillus strain. This is in line with the findings of Di Nunzio et al [ 21 ], who reported a significant increase in narirutin and didymin bioaccessibility by adding 8 log cfu mL −1 of L. salivarius to ortanique juice homogenized at 20 MPa. As was also argued by these authors, this result can be attributed to the ability of the microorganism to enhance the release of phenolic compounds linked to fibers and other components of the food matrix.…”
Section: Resultssupporting
confidence: 93%
“…As regards the vacuum impregnation liquid, the 0%_100 MPa was the one that best prevented the degradation of the flavonoids. A similar positive effect on the bioaccessibility of flavonoids as a result of the ortanique low pulp juice homogenization at 20 MPa was previously observed by Di Nunzio et al [ 21 ] and was explained in terms of the reduction in the particle size of the juice that facilitates the release of bioactives from the matrix.…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…Gas chromatographic traces and quantitative evaluations were obtained using Lab Solution software (Shimadzu, Kyoto, Japan) and normalized for the dilution factor due to the addition of digestive fluids. FAMEs from chemicals added during in vitro digestion system were subtracted, and bioaccessibility was calculated as FAME concentration in digested sample/FAME concentration in PRC before digestion × 100 [ 37 ].…”
Section: Methodsmentioning
confidence: 99%